Plant phenological research enhances ecological restoration - Buisson, Elise; Alvarado, Swanni T.; Le Stradic, Soizig; Morellato, Leonor Patricia C. (Restoration ecology, 2017)
While phenology data (the timing of recurring biological events) has been used to explain and predict patterns related to global change, and to address applied environmental issues, it has not been clearly identified as pertinent for restoration. This opinion article thus aims to raise awareness of the potential of phenology to enhance the quality of restoration projects and ecological restoration theory. We based our analysis on a systematic literature survey carried out in February 2014, searching the words “phenology” or “phenological” in books dealing with restoration, the term “phenolog*” in the journal Restoration Ecology, and the terms “restoration” and “phenolog*” in the database Web of Science until February 2014. We finally selected 149 studies relevant to our goals, and first classified them according to the context in which phenology was addressed. We then analyzed them within the framework of the five key steps of restoration projects: (1) the reference ecosystem; (2) biotic resources; (3) restoration methods; (4) monitoring; and (5) adaptive management. The literature survey showed that phenological information improved decision‐making in the few restoration projects in which it was incorporated. We thus advocate taking phenological data into account at all stages of restoration when appropriate: from the acquisition of baseline data on the reference ecosystem to treatment design, and from restoration action planning and timing to monitoring. Phenological data should at minimum be collected for sown, keystone, dominant, and/or rare species to improve restoration quality. Phenology studies and monitoring should be promoted in future restoration guidelines.